A Comparative Clinical Study of Matra Basti and Kati Basti with Nirgundi Taila in the Management of Kati Graha (Lumbar Spondylosis) - Devi, Sarita; Sharma, Gyan Prakash; Sharma, Meenakshi; Arun , N K (International Research Journal of Ayurveda & Yoga, 2022)
Lumbar spondylosis can be described as all degenerative conditions affecting the discs, vertebral bodies, and associated joints of the lumbar vertebrae. Spondylosis is very common disease (more than 1 crore cases per year in India). Low back pain affects approximately 60%-80% of adults and LS is responsible for about 10% of all the back pain conditions. Lumber spondylosis has been correlated with Kati Graha due to similarity of clinical manifestation. Kati Graha has been categorized under Vatika Nanatmaja Vyadhi. It is Shosha, Stambha and Shula predominant Vyadhi. This Clinical study shows that Nirgundi Taila Matra Basti and Nirgundi Taila Kati Basti give good result, but comparison in both therapies, Nirgundi Taila Matra Basti provided much better relief in the cardinal symptoms of LS.